2014
DOI: 10.14301/llcs.v5i3.295
|View full text |Cite
|
Sign up to set email alerts
|

How wrong were we? Dependent interviewing, self-reports and measurement error in occupational mobility in panel surveys

Abstract: Occupation is a central concept in sociology and economics, and individual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…With education, these results are in keeping with the current picture of teacher turn-over (Laming & Horne, 2013;Pinnington-Wilson, 2004;Williams, 2005). Teaching is seen as an occupationally-specific change option for older changers, and as an accepted occupational change pathway where maturity and experience could be seen as strengths (Anthony & Ord, 2008;Lee, 2011;Williams & Forgasz, 2009).…”
Section: Factors Relating To the Decision To Change And The Change Prsupporting
confidence: 77%
See 3 more Smart Citations
“…With education, these results are in keeping with the current picture of teacher turn-over (Laming & Horne, 2013;Pinnington-Wilson, 2004;Williams, 2005). Teaching is seen as an occupationally-specific change option for older changers, and as an accepted occupational change pathway where maturity and experience could be seen as strengths (Anthony & Ord, 2008;Lee, 2011;Williams & Forgasz, 2009).…”
Section: Factors Relating To the Decision To Change And The Change Prsupporting
confidence: 77%
“…Previous studies examining rates of mobility used self-reported job/occupation titles in conjunction with various occupational-classification scales to distinguish occupations and locate occupational change, but such research has various limitations as discussed in chapter 1 (Kambourov & Manovskii, 2008;Parrado et al, 2007;Perales, 2014). Names of occupations are inconsistent indicators of requisite skills-and-knowledge sets, and so poor measures of actual skillsand-knowledge set changes as Parrado et al (2014) reported.…”
Section: Methodological Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A transition matrix for the German SOEP tells us that only a small share of all workers is mobile across classes: on average, 12% in the low-skilled working class and 8% in the upper-middle class change class from one year to the next over our period of observation. Moreover, there is ample evidence that occupational changes are overestimated in panel surveys due to measurement errors (Perales 2014).…”
Section: Methods and Modelmentioning
confidence: 99%